Beyond Sustainability: Assessing the Regenerative Margins and Community Participation Gaps in Serangan Tourism - Dewa Ayu Diyah Sri Widari; Dewa Putu Oka Prasiasa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This research investigates the strategic evolution of Serangan Tourism Village, Bali, as it transitions from conventional sustainability paradigms toward a proactive regenerative framework. The study primarily aims to assessing regenerative margins and diagnose systemic gaps within local social governance. Employing a qualitative methodology, the investigation utilizes a robust analytical toolkit comprising Value Chain Analysis, Power-Interest Mapping, and Arnstein’s Ladder of Participation. Data derived from participatory observation, semi-structured in-depth interviews, and longitudinal document reviews were integrated through a comprehensive cross-analysis. The findings empirically confirm the attainment of a positive regenerative margin in Serangan, largely catalyzed by the marine conservation community’s restorative efforts. This achievement is underpinned by regenerative parallelism, a mechanism where the restoration of coral reefs and turtle habitats directly augments the destination's economic competitiveness. Despite these gains, a critical participation disparity remains; while conservation actors spearhead the regenerative transition, essential stakeholders most notably Local Culinary Community are relegated to the placation stage with limited decision-making agency. Such governance imbalances threaten the long-term resilience of regene-rative outcomes. This study contributes to the field by operationalizing regenerative parallelism as a functional metric for tourism development. Ultimately, the research concludes that enduring regenerative success necessitates fundamental governance restructuring, moving toward delegated power for local actors and the diversification of restorative funding through impact investment.